Artificial empathic interaction and social analgesia as a conceptual framework for chronic pain care - Parisa Gazerani (npj Digital Medicine, 2026)
Abstract Chronic pain is shaped by biological, psychological, and social processes, yet the role of perceived empathic interaction with artificial agents remains poorly understood. This Perspective proposes Artificial Empathic Interaction as a conceptual framework, introduces the concept of Artificial Social Analgesia as a hypothesized outcome of artificial empathic interaction, and presents the Artificial Empathic Interaction Model (AEIM) as a hypothesis-generating, empirically testable framework. It further outlines an interdisciplinary research agenda to investigate the potential mechanisms, opportunities, limitations, and ethical implications of artificial empathic interaction in digital medicine.